2012
DOI: 10.1158/1535-7163.mct-11-0607
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antigenic Peptides Based on H-2Kb–Restricted CTL Epitopes from Murine Heparanase Induce a Potent Antitumor Immune ResponseIn Vivo

Abstract: Accumulating research suggests that heparanase may be a universal tumor-associated antigen (TAA). Several heparanase T-cell epitopes from humans and mice have already been identified. However, because of low immunogenicity, polypeptide vaccines usually have difficulty inducing effective antitumor immune responses in vivo. In this study, to increase the immunogenicity of polypeptide vaccines, we designed and synthesized two four-branch multiple antigenic peptides (MAP) on the basis of mouse heparanase (mHpa) Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It has not yet been determined whether these hTERT single epitope vaccines mediate an immunodominant response. This uncertainty may be due to their low molecular weight, rapid decline, weak immunogenicity, and their ineffective processing and presentation on cancer cells (37). To overcome the above problems, various carrier proteins and fusion proteins were used as vectors for delivering T-cell epitopes, while there is a risk that foreign proteins with high molecular weights will induce the immune response, rather than the target polypeptides.…”
Section: Applications Of Htert-based Peptides For Cancer Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not yet been determined whether these hTERT single epitope vaccines mediate an immunodominant response. This uncertainty may be due to their low molecular weight, rapid decline, weak immunogenicity, and their ineffective processing and presentation on cancer cells (37). To overcome the above problems, various carrier proteins and fusion proteins were used as vectors for delivering T-cell epitopes, while there is a risk that foreign proteins with high molecular weights will induce the immune response, rather than the target polypeptides.…”
Section: Applications Of Htert-based Peptides For Cancer Vaccinesmentioning
confidence: 99%
“…hTERT peptides are processed and presented on the surface of DCs in the form of multiple-epitope that produce multiple CTL cell clones to induce an effective antitumor response using the MHC-I and -II pathways and avoid immune escape due to the loss of a single HLA allele. More attractively, the multiple antigenic peptide (MAP) system based on the core matrix lysine being coupled with four or eight strips of epitope monomer to form a branch-like structure, represents a unique way to generate anti-peptide antibodies (37). Theoretically, the MAP structure not only strengthens the specificity of the peptide chain structure and increases the molecular weight of the epitope peptides but also induces a high titer, high affinity antibody.…”
Section: Applications Of Htert-based Peptides For Cancer Vaccinesmentioning
confidence: 99%
“…As a result, these peptides can elicit stronger in vivo immune responses than linear peptides. 17 We recently reported that modification of the 8Q min epitope from the E7 protein by replacing the C-terminal CCKCD sequence with SSKSD or SKKKK substantially diminished its immunogenicity. In contrast, deletion of the CCKCD sequence did not have any negative influence on the epitope potency.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic T lymphocytes (CTLs) play a key role in immunity against tumors in vitro and in vivo [17][18][19]. CTLs can efficiently deliver tumor-associated antigens (TAAs) to the major histocompatibility complex (MHC) class I processing pathway of professional antigen-presenting cells (APCs), and especially dendritic cells (DCs) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%